Structural Sustainable Recycled Aggregate Concrete Production Under Environmental Conditions - Datta, Shuvo Dip; Sobuz, Md. Habibur Rahman; Sutan, Norsuzailina Mohamed; Islam, Shoaib (International Journal of Integrated Engineering, 2023)
The use of recycled aggregates (RA) in the concrete industry has become increasingly popular due to the reduction in natural aggregate (NA) consumption and the ability to reuse demolition waste. This research focuses on analyzing the performance of recycled aggregate concrete (RAC) cured with sodium sulfate (Na2SO4). Five different mixtures were created, varying from 0% RA without supplementary cementitious material (SCM), to 0%, 15%, 30%, and 45% substitution of NA with RA and SCM. The slump test was performed on all fresh RAC mixtures, which showed a decrease in slump with an increase in RA content. Both 5% Na2SO4 solution curing at 91 days and standard curing at 7, 28, and 91 days resulted in a reduction in compressive strength and ultrasonic pulse velocity (UPV) as the proportion of RA increased. Compared to standard curing, the compressive strength of specimens cured with 5% Na2SO4 solution at 91 days showed a decrease of approximately 5-7%. The UPV of SCM-based mixes showed 14-28% improvement with respect to normal aggregate concrete (NAC) in normal water curing. Furthermore, the SCM-included specimens have produced less deterioration in Na2SO4 immersion as SCM particles resist the severity of the dominant sulfate environment.